EVALUATING THE ROLE OF THE BALANCED SCORECARD IN ENHANCING HEALTHCARE ORGANIZATIONAL PERFORMANCE: A SYSTEMATIC REVIEW - Mohammad Raffy yusmar (LP2IHKI UMSurabaya, 2025)
Objective: The publication explores the use of the Balanced Scorecard (BSC) in healthcare, focusing on its benefits, challenges, and recent adaptations for sustainability, community engagement, and crisis management. It aims to provide recommendations to help healthcare organizations effectively use the BSC to improve their performance and service quality. Methods: This study conducts a systematic review of scientific publications on the Balanced Scorecard within the healthcare sector using the PubMed database. The search strategy employed the following keywords: (